2009
DOI: 10.2174/1874285800903010092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimicrobial Activity of Granulysin against Bacterial Biothreat Agents

Abstract: Granulysin is a cationic protein produced by human T cells and natural killer cells that can kill bacterial pathogens through disruption of microbial membrane integrity. Herein we demonstrate antimicrobial activity of the granulysin peptide derived from the active site against Bacillus anthracis, Yersinia pestis, Francisella tularensis, and Burkholderia mallei, and show pathogen-specific differences in granulysin peptide effects. The susceptibility of Y. pestis to granulysin is temperature dependent, being les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Endsley et al [14] suggested that augmentation of granulysin expression by cytotoxic lymphocytes, or therapeutic application of granulysin peptides, could constitute important strategies for protection against select agent bacterial pathogens. Investigations of the microbial surface molecules that determine susceptibility to granulysin may identify important mechanisms that contribute to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endsley et al [14] suggested that augmentation of granulysin expression by cytotoxic lymphocytes, or therapeutic application of granulysin peptides, could constitute important strategies for protection against select agent bacterial pathogens. Investigations of the microbial surface molecules that determine susceptibility to granulysin may identify important mechanisms that contribute to pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that granulysin contributes toward the defense mechanisms against mycobacterial infection [13]. Granulysin is a cationic protein that can kill bacterial pathogens through disruption of microbial membrane integrity [14].…”
Section: Introductionmentioning
confidence: 99%
“…28 Apart from cytotoxic granules forming pores in the target cell membrane leading to destruction of the physiologic membrane potential and allowing other lytic granules to enter and induce the death of the target cell, 36 there is also evidence that they may have a direct microbicidal effect on infectious pathogens. 38,39 The role of cytotoxic granules during cryptosporidiosis may thus be lysis of infected epithelial cells leading to release of live but immature Cryptosporidium organisms that are not able to re-infect the host and die because of interruption of their life cycle. Alternatively, the released cytotoxic granules may also have a parasitocidal effect on the organisms themselves, thus directly contributing to their elimination.…”
Section: Discussionmentioning
confidence: 99%
“…These include, for example, recombinant cystatin 9 [254] and small compounds prepared by ligandand structure-based drug design [255]. Currently, promising moderate therapy against tularemia comprises the immunosuppressive and/or immunomodulatory effects of antimicrobial peptides, such as human cathelicidin LL-37 peptide, novel synthetic hybrids designed from cecropin A, magainin II, granulysin peptides, or specific fly antimicrobial peptides as are attacin, cecropin, drosocin and drosomycin from Drosophila melanogaster [256][257][258][259]. These positively charged antimicrobial peptides are capable to disrupt the negatively charged bacterial membrane and limit the proliferation of microbes.…”
Section: Treatmentmentioning
confidence: 99%